Removal of the Retained Ventricular Catheter Using the Endoscopic Monopolar Instrument - Julia Pereira Muniz Pontes; Pedro Henrique Costa Ferreira-Pinto; Elington Lannes Simoes; Thaina Zanon Cruz; Jefferson Trivino Sanchez; Flavio Nigri (Case Reports in Surgery)
Background. Ventriculoperitoneal shunt (VPS) remains the main treatment for hydrocephalus. However, VPS revision surgery is very common. Here, we present a case in which the retained ventricular catheter was removed using the endoscopic monopolar instrument. Methods. We report a case of a 28-year-old female who presented with VPS obstruction. She had two previous shunt revision surgeries due to shunt obstruction. Eleven years after the last one, she presented an abdominal pseudocyst that indicated a total system removal. During VPS revision surgery, a retained ventricular catheter was observed. The endoscopic monopolar instrument was introduced into the retained catheter under direct view. Coagulations in a back-and-forth movement were applied to release inner catheter adhesions. After these steps, the catheter was removed, and a new one was placed through the same route. Results. The catheter was removed without complications, confirmed by the postoperative cranial computed tomography. The patient remained asymptomatic. Conclusion. The described technique was effective and avoided ventricular bleeding. Further studies are necessary to validate this method.